An Examination of Student Development Theory in the Context of Writing Instruction - Holli R. Leggette; Holly Jarvis Whitaker; Matt Miranda (Journal of Applied Communications, 2017)
The National Council of Teachers in English (2009) called for a reform of writing instruction models and theories. Addressing NCTE’s challenges to develop, design, and create models that inform curricula begins with examining writing instruction in the context of student development theory. Therefore, the purpose of this study was to modify a conceptual model, grounded in Chickering and Reisser’s (1993) theory of education and identity, to address NCTE’s challenge of developing evidence-based, empirically sound models for writing instruction. To accomplish this purpose, we conducted a philosophical examination of Chickering and Reissers’ theory in light of writing instruction. Since the 1970s, writing instruction has experienced three phases that situate the focus of instruction on specific functions of the writer and not on the holistic writer: (a) instruction for the hand (mechanics), (b) instruction for the mind (cognitive), and (c) instruction for the writer in context (social cognitive). Thus, through this examination, a fourth phase emerges—instruction of the person as a writer (holistic). Holistic developmental approaches to writing instruction focus on students’ perspectives of assignments, their navigation of the writing process throughout class experiences, their feedback on course content and assignments, and their development as people, professionals, and writers. Therefore, one way to address NCTE’s challenges and enhance learning outcomes is revising Leggette and Jarvis’ (2015) wagon wheel model because it shifts writing instruction away from teaching individual skills, abilities, and attributes of the writer and focuses more on teaching the holistic development of the writer.
Keywords: Curriculum; Student Development Theory; Writing Instruction